2013
DOI: 10.1073/pnas.1221803110
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic acetylcholine receptor activation blocks long-term potentiation at cerebellar parallel fiber–Purkinje cell synapses via cannabinoid signaling

Abstract: Muscarinic acetylcholine receptors (mAChRs) are known to modulate synaptic plasticity in various brain areas. A signaling pathway triggered by mAChR activation is the production and release of endocannabinoids that bind to type 1 cannabinoid receptors (CB1R) located on synaptic terminals. Using whole-cell patch-clamp recordings from rat cerebellar slices, we have demonstrated that the muscarinic agonist oxotremorine-m (oxo-m) blocks the induction of presynaptic long-term potentiation (LTP) at parallel fiber (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 52 publications
2
30
0
3
Order By: Relevance
“…Activation of muscarinic receptors can stimulate endocannabinoid synthesis, as it was shown on cerebellar Purkinje-cells [19] and in the hippocampus [9]. If this is the 13 case in the PPN, activation of M1 receptor increase endocannabinoid synthesis on neurons possessing it, and, in turn, this endocannabinoid acts on astrocytes [11].…”
Section: Discussionmentioning
confidence: 91%
“…Activation of muscarinic receptors can stimulate endocannabinoid synthesis, as it was shown on cerebellar Purkinje-cells [19] and in the hippocampus [9]. If this is the 13 case in the PPN, activation of M1 receptor increase endocannabinoid synthesis on neurons possessing it, and, in turn, this endocannabinoid acts on astrocytes [11].…”
Section: Discussionmentioning
confidence: 91%
“…It was suggested that mAChRs activation selectively targets presynaptic and postsynaptic LTP mechanisms and, though not directly, LTD penetrance could be enhanced indirectly by the prevention of coincident potentiation. Thus, cholinergic signaling in the cerebellum suppresses presynaptic LTP to prevent an upregulation of transmitter release that opposes the reduction of postsynaptic responsiveness (Rinaldo and Hansel, 2013).…”
Section: Role Of Ach In the Cerebellummentioning
confidence: 99%
“…Both mGluR5 and M 1 mAChR are Gq-coupled receptors, that engage similar downstream plasticity mechanisms 52 . M 1 mAChR regulate inhibitory and excitatory synapses via 2-AG and CB1R [53][54][55][56][57] . Thus, the current data add to the growing list of central synapses where 2-AG is the principal mediator of eCB mediated GPCR synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%